Genetic evidence for the subdivision of the arthropod limb into coxopodite and telopodite. - Gonzalez-Crespo, S.; Morata, G. (Development, 1996)
Arthropod appendages are thought to have evolved as outgrowths from the body wall of a limbless ancestor. Snodgrass, in his Principles of Insect Morphology (1935), proposed that, during evolution, expansion of the body wall would originate the base of the appendages, or coxopodite, upon which the most distal elements that represent the true outer limb, or telopodite, would develop. The homeobox gene Distal-less (Dll), which is required in the Drosophila appendages for development of distal regions, has been proposed to promote formation of telopodite structures above the evolutionary ground-state of non-limb or body wall. Here, we present evidence that another homeobox gene, extradenticle (exd), which is required for appropriate development of the trunk and the proximal parts of the appendages, represents a coxopodite gene. We show that exd function is eliminated from the distal precursors in the developing limb and remains restricted to proximal precursors throughout development. This elimination is important because, when ectopically expressed, exd prevents distal development and gives rise to truncated appendages lacking distal elements. Moreover, the maintenance of exd expression during larval stages, contrary to Dll, does not require the hedgehog (hh) signaling pathway, suggesting that the proximal regions of the appendages develop independently of hh function. Finally, we show that in the crustacean Artemia, exd and Dll are expressed in comparable patterns as in Drosophila, suggesting a conserved genetic mechanism subdividing the arthropod limb.